2013
DOI: 10.1111/1462-2920.12101
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of bacterial endosymbionts and bacteria–host co‐evolution in Gondwanan relict moss bugs (Hemiptera: Coleorrhyncha: Peloridiidae)

Abstract: Many hemipterans are associated with symbiotic bacteria, which are usually found intracellularly in specific bacteriomes. In this study, we provide the first molecular identification of the bacteriome-associated, obligate endosymbiont in a Gondwanan relict insect taxon, the moss bugs (Hemiptera: Coleorrhyncha: Peloridiidae), which represents one of the oldest lineages within the Hemiptera. Endosymbiotic associations of fifteen species of the family were analysed, covering representatives from South America, Au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 42 publications
1
38
0
Order By: Relevance
“…in the ovaries of the mother) (see e.g. Buchner, 1965;Szklarzewicz & Moskal, 2001;Szklarzewicz et al, 2006Szklarzewicz et al, , 2010Szklarzewicz et al, , 2013Sacchi et al, 2008;Kuechler et al, 2012Kuechler et al, , 2013Swiatoniowska et al, 2013 for further details). Both the histological studies of Buchner (1965Buchner ( , 1966Buchner ( , 1967) and more recent ultrastructural studies (Cheng & Hou, 2001;Szklarzewicz & Moskal, 2001;Szklarzewicz et al, 2006Szklarzewicz et al, , 2010Szklarzewicz et al, , 2013Sacchi et al, 2008;Kuechler et al, 2011Kuechler et al, , 2012Koga et al, 2012;Matsuura et al, 2012;Swiatoniowska et al, 2013) have revealed that the latter transmission of endosymbionts (termed transovarial transmission) may differ even in closely related groups of hemipterans.…”
Section: Discussionmentioning
confidence: 99%
“…in the ovaries of the mother) (see e.g. Buchner, 1965;Szklarzewicz & Moskal, 2001;Szklarzewicz et al, 2006Szklarzewicz et al, , 2010Szklarzewicz et al, , 2013Sacchi et al, 2008;Kuechler et al, 2012Kuechler et al, , 2013Swiatoniowska et al, 2013 for further details). Both the histological studies of Buchner (1965Buchner ( , 1966Buchner ( , 1967) and more recent ultrastructural studies (Cheng & Hou, 2001;Szklarzewicz & Moskal, 2001;Szklarzewicz et al, 2006Szklarzewicz et al, , 2010Szklarzewicz et al, , 2013Sacchi et al, 2008;Kuechler et al, 2011Kuechler et al, , 2012Koga et al, 2012;Matsuura et al, 2012;Swiatoniowska et al, 2013) have revealed that the latter transmission of endosymbionts (termed transovarial transmission) may differ even in closely related groups of hemipterans.…”
Section: Discussionmentioning
confidence: 99%
“…The diversity and abundance of insects feeding on xylem or phloem sap reflect the dominance of vascular plants in terrestrial ecosystems: symbionts provided the entry to a vast and expanding new niche that spread across the globe. As a counterexample, the Coleorrhyncha, which resembles other sap-feeding groups in originating around the same time (the Permian) and having an obligate symbiont, contains only about 24 species, reflecting ties to specific nonvascular plants (certain mosses) (13,14).…”
Section: Evolutionary Opportunities From Symbiosis: Ecological Benefimentioning
confidence: 99%
“…Once they reach the fourth instar, larvae cease feeding and prepare to molt into a non-feeding pupal stage. Mosquitoes, like many insects, rely on endosymbionts (microorganisms which provide nutrients or other beneficial functions) to grow and develop (Chouaia et al, 2012;Clark et al, 2010;Kafil et al, 2013;Kuechler et al, 2013;Moran et al, 2005b). For example, bacteria in the genus Buchnera are commonly endosymbionts of aphids and provide the aphid with essential amino acids (Douglas, 1998).…”
Section: Introductionmentioning
confidence: 99%